2022
DOI: 10.1161/jaha.121.023775
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity and Lower Respiratory Tract Infection Outcomes in Patients With Cardiovascular Disease

Abstract: Background To investigate the dose‐response association between physical activity and lower respiratory tract infection ( LoRI ) outcomes in patients with cardiovascular disease. Methods and Results Using the Korean National Health Insurance data, we identified individuals aged 18 to 99 years (mean age, 62.6±11.3 years; women, 49.6%) with cardiovascular disease who participated in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Numerous epidemiological studies have focused on the relationship between MVPA and pneumonia. 8 , 10 , [11] , [12] , [13] , [14] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] A review of 10 prospective cohort studies with over one million participants concluded that the risk for pneumonia (incidence and mortality) was 31% lower when comparing the most and least physically active groups. 32 These findings have been extended to those with diabetes 9 and cardiovascular disease (CVD).…”
Section: Acute Respiratory Infections (Aris)mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiological studies have focused on the relationship between MVPA and pneumonia. 8 , 10 , [11] , [12] , [13] , [14] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] A review of 10 prospective cohort studies with over one million participants concluded that the risk for pneumonia (incidence and mortality) was 31% lower when comparing the most and least physically active groups. 32 These findings have been extended to those with diabetes 9 and cardiovascular disease (CVD).…”
Section: Acute Respiratory Infections (Aris)mentioning
confidence: 99%
“… 32 These findings have been extended to those with diabetes 9 and cardiovascular disease (CVD). 43 A large population-based cohort study with more than one million Korean patients with CVD demonstrated a negative dose-response association of MVPA on mortality and hospitalization attributable to lower respiratory tract infections (LRTI), including pneumonia, bronchitis, and tuberculosis. 43 Each 500-MET min/week increase of MVPA was associated with a 22% and 13% reduced risk of LRTI mortality and hospitalization, respectively.…”
Section: Acute Respiratory Infections (Aris)mentioning
confidence: 99%
“… 77 Even low levels of physical activity in older patients with cardiovascular disease are associated with decreased mortality and hospitalization from pneumonia. 78 Thus, exercise training has been recommended to support pulmonary rehabilitation in chronic disease management. 79 …”
Section: Exercise Protects the Integrity Of Barriersmentioning
confidence: 99%
“…Although moderate exercise increases immunity, more intense regimens can cause temporary dips in immunity, increasing the risk of viral infections [4,119]. Upper respiratory tract viral infections are a significant cause of breaks in training and can result in the cancellation of a much-anticipated sporting event [120,121]. As well as being uncomfortable, intense exercise during a cold or flu infection is unwise as it can be associated with acute virus-induced skeletal and heart muscle damage, so it is not wise to train during the infective period [120].…”
Section: Anti-viral Properties: Avoiding Breaks In Training From Cold...mentioning
confidence: 99%